Non-vitamin K Antagonist Oral Anticoagulants and Cognitive Impairment in Atrial Fibrillation: Insights From the Meta-Analysis of Over 90,000 Patients of Randomized Controlled Trials and Real-World Studies - Zhang, Chi; Gu, Zhi-Chun; Shen, Long; Pan, Mang-Mang; Yan, Yi-Dan; Pu, Jun; Liu, Xiao-Yan; Lin, Hou-Wen (Frontiers in Aging Neuroscience, 2018)
Background The relationship between the use of non-vitamin K antagonist oral anticoagulants (NOACs) and the impairment of cognition in atrial fibrillation (AF) remains unknown. Methods A comprehensive database search of Medline, Embase, Cochrane Library databases and ClinicalTrials.gov Website was performed for randomized controlled trials (RCTs) reporting cognitive impairment events and observational nationwide database studies reporting adjusted hazard ratio (HR) in AF patients with NOACs. The primacy outcome was a composite of any cognitive impairment. Summary HRs and 95% confidence intervals (95%CI) were calculated using fixed- and random-effects models. Subgroup analyses were undertaken according to individual NOACs, study types and duration of follow-up. Results Finally, 8 studies including 97,595 patients (77,643 patients in 6 RCTs and 19,952 patients in 2 observational database studies) met the inclusion criteria, among which 55,337 (56.7%) patients receiving NOACs and 42,258 (43.3%) patients receiving vitamin K Antagonists (VKAs) or acetylsalicylic acid. Results showed a borderline significant association between the use of NOACs and the lower risk of cognitive impairment when compared with VKAs/ acetylsalicylic acid (HR: 0.80, 95%CI: 0.63-0.98 for fixed-effects model; HR: 0.77; 95%CI: 0.53-1.01 for random-effects model), with no significant heterogeneity between the studies (I2=39.4%, P=0.12). The results were consistent across the key subgroups (Pinteraction>0.05 for each). Conclusions The results indicated that the use of NOACs might bring a lower tendency on the risk of cognitive impairment in comparison to VKAs/ acetylsalicylic acid, and further RCTs and real-world studies are urgent to obtain a robust result.